A Single Institution's Experience With Robotic Minor and Major Hepatectomy. Issue 5 (May 2023) - Sucandy, Iswanto; Jacoby, Harel; Crespo, Kaitlyn; Syblis, Cameron; App, Samantha; Ignatius, Joshua; Ross, Sharona; Rosemurgy, Alexander
Background: Minimally invasive liver resection is gradually becoming the preferred technique to treat liver tumors due its salutary benefits when compared with traditional "open" method. While robotic technology improves surgeon dexterity to better perform complex operations, outcomes of robotic hepatectomy have not been adequately studied. We therefore describe our institutional experience with robotic minor and major hepatectomy. Materials and Methods: We prospectively study all patients undergoing robotic hepatectomy from 2016 to 2020. Results: A total of 220 patients underwent robotic hepatectomy. 138 (63%) were major hepatectomies while 82 (37%) were minor hepatectomies. Median age was 63 (62 ± 13) years, 118 (54%) were female. 168 patients had neoplastic disease and 52 patients had benign disease. Lesion size in patients who had undergone minor hepatectomy was 2 (3 ± 2.5) cm, compared to 5 (5 ± 3.0) cm in patients who undergone major hepatectomy ( P < .001). 97% of patients underwent R0 resections while none of the patients had R2 resection. Operative duration was 226 (260 ± 122.7) vs 282 (299 ± 118.7) minutes ( P ≤ .05); estimated blood loss was 100 (163 ± 259.2) vs 200 (251 ± 246.7) mL ( P ≤ .05) for minor and major hepatectomy, respectively. One patient had intraoperative bleeding requiring "open" conversion. Nine (4%) patients had experienced notable postoperative complications and 2 (1%) patients died postoperatively. Length of stay was 3 (5 ± 4.6) vs 4 (5 ± 2.8) days for minor vs major hepatectomy ( P = .84). Reoperation and readmission rate for minor vs major hepatectomy was 1% vs 3% ( P = .65) and 9% vs 10% ( P = .81), respectively. Discussion: Robotic major hepatectomy is safe, feasible, and efficacious with excellent postoperative outcomes.